FRI0323 Cronic Non-Bacterial Osteomyelitis (CNO) in a Cohort of Pediatric Patients: Clinical, Biological and Radiological Response to Treatment with Anakinra. (9th June 2015) - Pardeo, M.; Marafon, D.P.; Messia, V.; Nicolai, R.; Bracaglia, C.; De Benedetti, F.; Insalaco, A.
Abstract : Background: Chronic nonbacterial osteomyelitis (CNO)is the most common autoinflammatory bone disorders in childhood (1). CNO remains a diagnosis of exclusion because of the absence of specific clinical or laboratory findings.An important role in the diagnosis could be provided by whole body imaging techniques as TC-99 bone scintigraphy and/or whole body MRI. The treatment is not standardized;non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, bisphosphonates and tumour necrosis factor neutralizing agents have been used until now with variable response (2). Objectives: To describe clinical, biological and radiological response to treatment with IL-1 receptor antagonist (anakinra) in a cohort of patients with CNO. Methods: Seven patients with CNO refractory to NSAIDs, glucocorticoids and bisphosphonate (pamidronate) were treated with anakinra for at least 6 months in our institution. Response of treatment was evaluated assessing clinical manifestations (pain, local swelling, functional impairment), laboratory findings (C-reactive protein [CRP], erythrocyte sedimentation rate [ESR] and serum amyloid A level [SAA]) and number of bone lesions on TC-99 bone scintigraphy at the start of treatment and in a 6 months follow-up. Results: Seven patients (4 females and 3 males) were included in this study. The median age at diagnosis was 9.7 years (IQR 7.8-14.7) and the median age before starting anakinra treatment was 13.3 years (IQR 8.0-15.9). All the patients were treated with NSAIDs and bisphosphonates as first-line therapy. Glucocorticoid therapy was required in one patients with concomitant recurrent fever and pleural effusion. These patients did not respond satisfactorily and we decide to use anakinra (2 mg/kg/day) to control disease activity. At the start of treatment 7/7 patients (100%) had pain, 3/7 (43%) local swelling and 5/7 (71%) functional impairment; at 6 months of follow up 6/7 patients (86%) were completely asymptomatic, with one patient complaining of arthralgia. Before starting anakinra the median CRP, ESR and SAA were 2.7 mg/dl (IQR 1.7-4.9) 26 mm/h (IQR 12-46) and 53 mg/dl (IQR 27-112); at 6 months 5/7 patients (71%) have normalized CRP, ESR and SAA, 2/7 had a decrease in inflammatory markers. Before anakinra 59 osseous lesions were detected on TC-99 bone scintigraphy. After 6 months of therapy 24/59 lesions (40%) had completely resolved, 1/59 lesions (2%) had partially improved and 29/59 lesions (49%) remained stable. In two patients with persistent high biological inflammatory markers, new lesions (14) developed during treatment. Conclusions: Our data suggest that anakinra appears effective in CNO patient, who have not responded to standard of care, in controlling symptoms and laboratory findings, although subclinical bone inflammation was still detectable by bone scintigraphy after 6 months of treatment. Long-term follow-up studies with a larger number of patients are needed. References: Sara M. Stern, Polly J. Ferguson. Autoinflammatory Bone Diseases. Rheum Dis Clin N Am 39 (2013) 735-749. H J Girschick, P Raab, S Surbaum, A Trusen, et al. Chronic non-bacterial osteomyelitis in children. Ann Rheum Dis 2005;64:279-285. Disclosure of Interest: None declared